An iterative approach to promoting departmental wellbeing during COVID‐19. Issue 1 (29th August 2021) - Acai, Anita; Gonzalez, Andrea; Saperson, Karen
Abstract: Rationale, Aims, and Objectives: Addressing wellbeing among learners, faculty, and staff during the COVID‐19 pandemic is a challenge for many clinical departments. Continued and systemic supports are needed to combat the pandemic's impact on mental health and wellbeing. This article describes an iterative approach to conducting a needs assessment and implementing a COVID‐19‐related wellness initiative in a psychiatry department. Methods: Development of the initiative followed the Plan‐Do‐Study‐Act (PDSA) quality improvement cycle and was informed by Shanafelt and colleagues' framework for supporting healthcare workers during the COVID‐19 pandemic. Key features included the establishment of a Wellness Working Group, the curation of relevant resources on the Department's website, and the deployment of regular, monthly surveys that informed the creation of further supports, such as a weekly online drop‐in support group. Results: Survey response rates ranged from 22% to 32% ( n  = 90‐127) throughout our initiative. Across multiple surveys, approximately 80% of respondents reported feeling supported or very supported by the Department, and 90% were satisfied or very satisfied with the quantity and quality of information provided. Our support group and resources page were accessed by nearly one‐quarter and one‐third of respondents, respectively, with satisfaction rates of 81% or higher. Consistent with the Department's mandate, ensuring equity was a key focus of the Working Group throughout its operations. Conclusions: There is potential for this model to be scaled to create a faculty‐wide, institution‐wide, or regional approach to addressing wellbeing. Other departments may also wish to adopt similar approaches to supporting their members during this challenging time.